2017
DOI: 10.1080/20477724.2017.1299831
|View full text |Cite
|
Sign up to set email alerts
|

Association of enteric parasitic infections with intestinal inflammation and permeability in asymptomatic infants of São Tomé Island

Abstract: The cumulative effect of repeated asymptomatic enteric infections on intestinal barrier is not fully understood in infants. We aimed to evaluate the association between previous enteric parasitic infections and intestinal inflammation and permeability at 24-months of age, in asymptomatic infants of São Tomé Island. A subset of infants from a birth cohort, with intestinal parasite evaluations in at least four points of assessment, was eligible. Intestinal inflammatory response and permeability were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 87 publications
(145 reference statements)
3
21
0
Order By: Relevance
“…This is important for further studies evaluating fecal S100A12 concentrations in patients with suspected chronic gastrointestinal inflammation [ 27 ]. These findings are consistent with the results of a previous investigation in asymptomatic children showing fecal S100A12 concentrations to only have a tendency to be increased with concurrent Giardia duodenalis and helminth infections [ 20 ]. Also, the concentrations of fecal S100A12 measured in the study by Garzón et al [ 20 ] were comparable to those concentrations detected in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is important for further studies evaluating fecal S100A12 concentrations in patients with suspected chronic gastrointestinal inflammation [ 27 ]. These findings are consistent with the results of a previous investigation in asymptomatic children showing fecal S100A12 concentrations to only have a tendency to be increased with concurrent Giardia duodenalis and helminth infections [ 20 ]. Also, the concentrations of fecal S100A12 measured in the study by Garzón et al [ 20 ] were comparable to those concentrations detected in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Only very few studies have been published about the effect of enteric parasite infections [ 20 ] or enteropathogenic viruses [ 17 ] on fecal S100A12 concentrations in humans, and the role of S100A12 in parasite and viral infections is difficult to study using a traditional rodent animal model due to the lack of S100A12 in rodents [ 21 ]. Although the function of S100A12 may be species-specific, the existence of a homologue of this calgranulin protein in dogs [ 22 ] appears to render the dog an ideal model for studying S100A12 biology and the RAGE-S100A12 axis in human patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies have failed to demonstrate reproducible changes in these markers following interventions. Nutritional supplementation with vitamin A [19], zinc [20,21], multiple micronutrients [22], alanlyl-glutamine [23][24][25] or dietary supplementation [26,27] have produced transient or inconsistent improvements. Interventions aimed at ameliorating intestinal inflammation, permeability or microbiome disruption have also been unsuccessful, including probiotics [28], antibiotics [29], long-chain polyunsaturated fatty acids [30], lactoferrin with lysozyme [31], and albendazole plus zinc [32].…”
mentioning
confidence: 99%
“…In the context of this article, we define a symptomatic infection, i.e., giardiasis disease, as being characterized by acute gastrointestinal complaints, like diarrhea, abdominal pain, nausea, and vomiting (Adam, 2001 ; Ankarklev et al, 2010 ) and we like to distinguish it from asymptomatic infections defined by the absence of such acute symptoms. Asymptomatic infections according to this definition would include infections that—particularly if recurring—result in malabsorption/malnutrition phenotypes or may represent pure colonization without any pathology, which was recently shown by Garzon et al ( 2017 ) on asymptomatic children, who found no correlation between Giardia -infection and barrier dysfunction, but only of barrier dysfunction and wasting and stunting. However, infections may also trigger post-infectious syndromes such as irritable bowel disease (D'Anchino et al, 2002 ; Wensaas et al, 2012 ; Hanevik et al, 2014 ; Litleskare et al, 2015 ; Halliez et al, 2016 ; Nakao et al, 2017 ).…”
Section: The Challenge: Symptomatic Vs Asymptomatic Infectionsmentioning
confidence: 99%